Variation of Charging Parameters on A dust Grain in Laboratory Plasma by Using Orbital-Motion Limited Theory - Jassim, M.K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Using orbit- motion limited theory, as the exact theory in calculating the ion and electron current in dusty plasma, the variations of charge number on a dust grain in Ar-plasma are studied by changing various charging parameters. Most of dependences of charge number on plasma parameters in this paper take into account the close packed effect.